Kontribusi Penguasaan Kosakata terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X SMA Negeri 2 Koto XI Tarusan - Savira Nurmalita; Mohd. Hafrison (Universitas Negeri Padang, 2022)
The purpose of this study is to describe vocabulary mastery, exposition text writing skills and analyze whether there is a contribution between vocabulary mastery to the exposition text writing skills of class X students of SMA Negeri 2 Koto XI Tarusan. This type of research is quantitative research with descriptive methods. The contribution is calculated by the determinant coefficient formula, using a correlational research design. The population of this study was class X students of SMA Negeri 2 Koto XI Tarusan with a study sample of 52 people. This research instrument is an objective test for vocabulary mastery and a performance test for exposition text writing skills. The result of this study is that the vocabulary mastery of class X students is at a qualification of more than enough in the range of 66-75 on a scale of ten with an average count of 73.75, the exposition text writing skills of class X students are in good qualifications in the range of 76-85 on a scale of ten with an average count of 83.74, the mastery of vocabulary of class X students contributed by 55.35% to the exposition text writing skills of class X students with H0 in the research rejected, while H1 is accepted because the calculation is greater than the ttable (7.87 >1.68). Thus it is concluded that mastery of vocabulary contributes to the skill of writing expositional texts at a significant level of 95%, that is, the calculation is greater than the ttabel with dk =n-1.